110 Acne, Folliculitis and Post-Operative Infection Rates of Penile Prosthetic Implants. Issue 1 (1st April 2022) - Choi, E; Barnard, J; Horns, J; Paudel, N; Das, R; Yafi, F; Hotaling, J
ABSTRACT: Introduction: Acne vulgaris is the inflammation of the pilosebaceous unit due to overgrowth of Propionibacterium acnes while folliculitis is inflammation of the hair follicle commonly due to Staphylococcus aureus. Whether these microbes are pathogenic in urologic procedures is yet to be determined. Objective: In this database study, we investigated whether acne or folliculitis were associated with an increased risk of post-surgical infection in men who received a penile prosthetic implant (PPI). Methods: The IBM MarketScan® Claims dataset was utilized to assess penile prosthesis encounters. Men 18-years and older who received a PPI were included in this study. Acne and folliculitis were analyzed separately as independent variables. Demographic factors that influence infection rates were examined including age, immunosuppressed status, coronary artery disease (CAD), diabetes, smoking status, and spinal cord injury (SCI). (Table 1a-b). A log-rank test of Kaplan-Meier curves determined whether having acne or folliculitis was significantly associated with time to post-operative infection within 6 months. Cox Proportional-Hazard models included covariates deemed most clinically relevant. Results: Our analysis included 17, 031 men who received a PPI. When analyzing men with acne, aside from being younger (59.9 vs 62.4, p<0.001), there were no statistical difference compared to men without (Table 1a). By 6 months, having acne was not associated with increased rates of infection (Figure 1a, Table 2a). Men with folliculitis were found to have significantly higher rates of diabetes, immunocompromised status, and CAD compared to men without (Table 1b). Having folliculitis was not associated with increased rates of infection by 6 months even after adjusting for covariates (Figure 1a, Table 2b). Conclusions: There appears to be no association between acne and folliculitis and rates of PPI infection. These findings allude to the difficulty in predicting which microorganism within the natural skin flora may be inoculant and which are pathogenic in surgical incisions. Furthermore, infection rates of PPI's may be due to other factors such as intraoperative aseptic techniques and post-operative hygiene. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Antares Pharma, Clarus Therapeutics, Coloplast, Promescent, Viome